Chronic pain in a family doctor practice – meaning, assessment, and therapeutic options - Prokop, Dominika; Borek, Mikołaj; Baran, Jan; Rowiński, Dawid; Sikora, Oliwia; Chamera-Cyrek, Katarzyna; Podczerwińska, Aneta; Kuzminski, Clara (Nursing Problems / Problemy Pielęgniarstwa, 2024)
Pain is a subjective, negative experience originating from stimuli that are currently or potentially damaging to the body’s tissues. Proper assessment of pain intensity is a clinically significant factor determining the further course of action for a family doctor at the initial therapeutic stage. Pharmacotherapy remains the primary therapeutic method but requires caution and consideration of specific adjustments during particular life stages of patients – paediatric and geriatric populations, as well as in pregnant or breast-feeding women. According to the recommendations of the International Association for the Study of Pain, patients with chronic pain should be treated interdisciplinarily, incorporating not only pharmacological treatments but also psychological, rehabilitative, and other non-pharmacological methods. Appropriately tailored therapeutic management is crucial because insufficient pain relief negatively affects the central nervous system, potentially leading to behavioural changes, emotional and psychological disorders, cognitive dysfunctions, abnormalities in cerebral blood flow, and a decrease in the number of neurons.